A Design of a hydraulic trolley to reduce work risks in gram transfer activities at PT XYZ - Rahayu, Mira; Malik, Ade (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
Material Handling Equipment (MHE) is a tool used to facilitate worker activities when doing heavy work. Material Handling Equipment (MHE) is also very helpful for workers in reducing the workload caused by less ergonomic activities that can cause worker fatigue. At PT XYZ there is activity of transferring grams onto trucks with trolleys. In the activity of transferring gram ± 60 minutes for transferring gram onto the truck. The worker's posture when using the trolley has a REBA value of 12 which means Very High Risk. Therefore this study focuses on redesigning the trolley with consideration of REBA analysis using the Kansei Engineering approach. The results of the redesign get a REBA value of 3, it can be concluded that the proposed trolley is better than the existing trolley